Safety and efficacy of Monimax® (monensin sodium and nicarbazin) for chickens for fattening and chickens reared for laying. (14th November 2018) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The coccidiostat Monimax ® (monensin sodium and nicarbazin) is considered safe for chickens for fattening and chickens reared for laying at the highest use level of 50 mg monensin and 50 mg nicarbazin/kg complete feed. This conclusion is extended to chickens reared for laying. For both active substances, the metabolic pathways in the chicken are similar to those in the turkey and rat. Nicarbazin, when ingested, is rapidly split in its two components dinitrocarbanilide (DNC) and 2‐hydroxy‐4, 6‐dimethylpyrimidine (HDP) which behave independently. Monimax ® does not represent a genotoxic risk. No safety concerns would arise from the nicarbazin impurities p ‐nitroaniline and methyl(4‐nitrophenyl) carbamate. The lowest no observed effect level (NOEL) identified for monensin sodium in a developmental study in rabbits is 0.3 mg monensin sodium/kg body weight (bw) per day for maternal toxicity in rabbits. The lowest no observed adverse effect level (NOAEL) identified in a 52‐week study in rat using DNC + HDP was 20 mg DNC + 8 mg HDP/kg bw per day based on the absence of microcrystals in urine and related microscopic renal observations. No significant interaction between monensin sodium and nicarbazin is expected from toxicological studies. The use of Monimax ® at the highest proposed dose will not pose a risk to persons consuming animal products from treated chickens for fattening. This conclusion is extended to chickens reared for laying. No withdrawal time is required for Monimax ® in chickens for fattening. Residue data comply with the established maximum residue limits (MRLs) for monensin and DNC. Based on the available data, the FEEDAP Panel cannot conclude on the safety of Monimax ® for the environment. Monimax ® has the potential to control coccidiosis in chickens for fattening at a minimum concentration of 40 mg monensin and 40 mg nicarbazin/kg complete feed.